Protecting the Digital Ecosystem: AI’s Dual Role in Machine Identity Security - Sushant Chowdhary (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The convergence of artificial intelligence, machine identities, and privileged access management represents a pivotal shift in the cybersecurity landscape, introducing unprecedented challenges for modern organizations. This comprehensive analysis examines how artificial intelligence-powered threats are revolutionizing attack vectors through automated social engineering, adaptive malware, and intelligent ransomware capabilities, while simultaneously transforming defensive strategies through enhanced threat detection and human-artificial intelligence collaboration. This article explores the critical intersection of machine identity proliferation - encompassing applications, containers, and Internet of Things devices - with traditional security frameworks, highlighting the complexities of certificate management, access controls, and continuous monitoring in automated environments. Furthermore, it investigates the evolution of privileged access management as it adapts to secure both human and machine identities, addressing challenges such as artificial intelligence-augmented privilege escalation and insufficient monitoring capabilities. Special attention is given to emerging trends, including artificial intelligence-driven attack simulation, unified identity and access management solutions, and evolving regulatory requirements, providing organizations with actionable insights for developing resilient security strategies in an increasingly complex digital ecosystem.